2005
DOI: 10.1088/0960-1317/15/8/003
|View full text |Cite
|
Sign up to set email alerts
|

Study on rheological behavior of polymer melt flowing through micro-channels considering the wall-slip effect

Abstract: Micro molding is attracting more attention nowadays and determination of the rheological behavior of the polymer melt within micro structured geometry is considered to be very important for the accurate simulation modeling of micro molding. The lack of commercial equipment is one of the main hurdles in the investigation of micro melt rheology. In this study, the melt viscosity measurement system for PS (polystyrene) melt flowing through a micro-channel was established using a micro-channel mold operated at a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
0
4

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(81 citation statements)
references
References 11 publications
1
76
0
4
Order By: Relevance
“…Generally, wall slip can reduce the shear stress needed to force a polymer melt thought the slit cavities and consequently can serve to reduce the viscosity. Experimental work by Chien et al [9] and simulation by Yao & Kim [24] both confirm that wall slip can significantly reduce the viscosity of polymer melts.…”
Section: Interpreting Slit Thickness Dependent Viscositymentioning
confidence: 90%
See 1 more Smart Citation
“…Generally, wall slip can reduce the shear stress needed to force a polymer melt thought the slit cavities and consequently can serve to reduce the viscosity. Experimental work by Chien et al [9] and simulation by Yao & Kim [24] both confirm that wall slip can significantly reduce the viscosity of polymer melts.…”
Section: Interpreting Slit Thickness Dependent Viscositymentioning
confidence: 90%
“…This was attributed to molecular structure. Chien et al [9] developed a series of micro-channels in a die that was embedded in a mold in order to study the rheological behavior of polymer melts under isothermal conditions using an injection molding machine. They found that the viscosity of polymer melts in the micro-channels is significantly lower than that measured when using a conventional capillary rheometer.…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations report a series of measurement of melt viscosity within small dimension geometries using high-fluidity amorphous ABS and PS resin [28,29], and high-low density PE, as well as high crystallinity POM resin [30]. From the measured pressure drop obtained from pressure transducers and melt volumetric flow rate, it is possible to calculate the viscosity values.…”
Section: Analysis On the Polymeric Materials And Their Selectionmentioning
confidence: 99%
“…The rheological data used in current packages are obtained from macroscopic experiments and they are not suitable for modelling microscale flows. In fact, when flowing in micro channels a polymer has a strong tendency to slip [3]. If a classic no-slip boundary condition is used in current packages, the consequences of wall slip cannot be predicted.…”
Section: Introductionmentioning
confidence: 99%